Counselling and knowledge on iron and folic acid supplementation (IFAS) among pregnant women in Kiambu County, Kenya: a cross-sectional study [version 3; peer review: 2 approved, 1 approved with reservations] - Mary Kamau; Samuel Kimani; Waithira Mirie (AAS Open Research, 2019)
Background: The increased demand for iron and folic acid during pregnancy is not met through diet due to insufficiency or reduced bioavailability of nutrients among women from low income countries. Thus, iron and folic acid supplementation (IFAS) is a promising interventional strategy for control of anaemia during pregnancy. Kenya adopted the global IFAS intervention with a target of 80% coverage by 2017, however, the compliance remains low. Increasing awareness, counselling, communication and community education on IFAS have improved compliance among pregnant women. Thus, we aimed to determine: IFAS knowledge, availability, practices, and content of IFAS counselling among pregnant women attending health facilities in Kiambu County, Kenya. Methods: A cross-sectional study involving 364 pregnant women aged 15-49 years. A two stage cluster sampling, including one sub-county and five public health facilities were used. A pre-tested, structured questionnaire consisting of socio-demographic data, maternal knowledge and counselling on IFAS was used. An observation checklist was used to observe practices and content of antenatal counselling session in each facility. Data was analysed using STATA in which descriptive and inferential statistics were computed. Results: Of 364 respondents, less than half (40.9%) scored high on knowledge on IFAS. Women who were counselled on duration of IFAS intake, side effects, and their mitigation were more likely (p <0.005) to have high IFAS knowledge. Although all the health facilities had varied IFAS posters displayed, none had key IFAS counselling documents. Conclusion: Less than half of the pregnant women had high IFAS knowledge, IFAS documents were scarce in health facilities, IFAS counselling information in different health facilities was limited and varied, and content of counselling was associated with levels of knowledge on IFAS. This underscores the need to strengthen focused and targeted IFAS counselling for pregnant women and standardization of counselling messages to improve compliance and pregnancy outcomes.